Preliminary investigation of novel tetra-tailed macrocycle amphiphile based nano-vesicles for amphotericin B improved oral pharmacokinetics. (12th November 2018) - Ali, Imdad; Rehman, Jawad ur; Ullah, Shafi; Imran, Muhammad; Javed, Ibrahim; El-Haj, Babiker M.; Saad Ali, Heyam; Arfan, Muhammad; Shah, Muhammad Raza
Abstract: Supramolecular macrocycles-based drug delivery systems are receiving wider recognition due to their self-assembly into nanostructures with unique characteristics. This study reports synthesis of resorcinarene-based novel and biocompatible amphiphilic supramolecular macrocycle that self-assembles into nano-vesicular system for Amphotericin B (Am-B) delivery, a model hydrophobic drug. The macrocycle was synthesized through a two-step reaction and was characterized with 1 H NMR and mass spectrometric techniques. Its biocompatibility was assessed in cancer cell lines, blood and animals. Its critical micelle concentration (CMC) was determined using UV spectrophotometer. Am-B loaded in novel macrocycle-based vesicles were examined according to their shape, size, surface charge, drug entrapment efficiency and excepients compatibility using atomic force microscope (AFM), Zetasizer, HPLC and FT-IR spectroscopy. Drug-loaded vesicles were also investigated for their in-vitro release, stability and in-vivo oral bioavailability in rabbits. The macrocycle was found to be nontoxic against cancer cells, haemo-compatible and safe in mice and revealed lower CMC. It formed mono-dispersed spherical shape vesicles of 174.4 ± 3.78 nm in mean size. Vesicles entrapped 92.05 ± 4.39% drug and were stable upon storage with gastric-simulated fluid and increased the drug oral bioavailability in rabbits. Results confirmed novel macrocycle as biocompatible vesicular nanocarrier for enhancing the oral bioavailability of lipophilic drugs.